Role Of Artificial Intelligence In Accounting: A Quantitative Economic Analysis Of Nigeria Financial Markets’ Future - Abdullahi Ya'u Usman; Abalaka, James Nda; Sulaiman Taiwo Hassan (International Forum of Researchers and Lecturers, 2025)
In today’s fast-evolving technological landscape, this study examines the profound integration of Artificial Intelligence (AI) into accounting and its far-reaching effects on the future of Nigeria financial markets. The incorporation of AI represents a fundamental shift in accounting, moving beyond conventional practices and ushering in unprecedented efficiency and advanced analytical capabilities. This transformation is instrumental in redefining accounting standards and influencing the broader economic dynamics of the financial sector. This paper aims to analyze the complex role of AI in accounting, evaluating its benefits, obstacles, and long-term potential. By connecting technological advancements with real-world accounting applications, the study provides an in-depth exploration of how AI is revolutionizing financial processes, its economic impact on Nigeria markets, and the balance between its advantages and inherent challenges. Additionally, the research proposes actionable strategies for optimizing AI adoption in accounting. The findings highlight that AI integration marks a critical advancement in accounting, improving precision, productivity, and strategic decision-making. Nevertheless, it also introduces hurdles such as workforce reskilling and ethical dilemmas. To address these challenges, the study recommends educational enhancements, policy adjustments, and cross-disciplinary cooperation to maximize AI’s potential in accounting. As a foundational contribution, this paper presents a compelling discussion on AI’s transformative role in accounting and its wider economic consequences, paving the way for future research and practical applications.